Effects of a Bt-based insecticide on the functional response ofCeraeochrysa cinctapreying onPlutella xylostella - Oliveira Pimenta, Isabela Cristina de; Silva Nunes, Gilmar da [UNESP]; Magalhaes, Gustavo Oliveira de [UNESP]; Santos, Nathalia Alves dos; Pinto, Matheus Moreira Dantas [UNESP]; De Bortoli, Sergio Antonio [UNESP] (Springer, 2020)
Plutella xylostella, is the main pest infestingBrassicacrops, and products based onBacillus thuringiensis(Bt) are frequently used in strategies for its biocontrol. The present study aimed to evaluate whether a Bt-based bioinsecticide affects the predation behavior ofCeraeochrysa cinctawhen preying onP. xylostella. Three larval instars of the predator and the eggs and second-instar larvae of the moth were used, with the prey either untreated or treated with a Bt-based product (Xentari (R)). Results showed that, the first larval instar ofC. cinctapresented a type II functional response when preying upon untreated eggs, and a type III response when preying upon Bt-treated eggs, while the second and third instars presented type II and III responses, respectively, in both situations. The predator's first and third larval instars presented a type II functional response when preying upon untreated larvae and a type III response when preying upon Bt-treated larvae. However, the predator's second-instar larvae showed a type II response in both treatments. The results obtained allowed us to conclude that the Bt-based insecticide tested affects the predation behavior of the first-instar larvae ofC. cinctaon eggs and of both the first- and third-instar larvae of this predator onP. xylostellalarvae.
Keywords: Bacillus thuringiensis; Chrysopids; Integrated pest management; Diamondback moth; Trophic interactions